Feasibility of Physical Activity Assessment with Wearable Devices in Children Aged 4–10 Years—A Pilot Study - Müller, Jan; Hoch, Anna-Maria; Zoller, Vanessa; Oberhoffer, Renate (Frontiers in Pediatrics, 2018)
Objective: Physical activity (PA) is associated with multiple beneficial health outcomes. Unfortunately, current studies report an alarming decrease of PA throughout all age groups. This study aims to assess general feasibility and PA levels of kindergarten and primary school children with wearable technology specifically manufactured for young children. Patients and methods: From April 2017 to August 2017 a total of 59 children (7.1 ± 1.7 years, 34 girls) recorded their PA for seven consecutive day wearing a wearable bracelet (Garmin vivofit jr). Afterwards they filled out a short, child-oriented questionnaire to rate the feasibility. Results: The general feasibility of the devices was rated as rather well regarding size, materials and wearing comfort. Moreover, children achieved a mean of 83 ± 18 minutes of moderate-to-vigorous physical activity (MVPA) and 12.202 ± 2.675 steps per day on a weekly average. Therefore, 52 (88.1%) children, and almost all boys (96%), fulfilled the WHO criteria of 60 minutes of MVPA per day on a weekly average. Conclusions: Wearables bracelets seem to be feasible devices for PA assessment even in young children. Nevertheless, their potential to increase PA for primary and secondary prevention of cardiovascular disease, as well as the long-term compliance needs to be clarified in further studies.